Tumor infiltrating neutrophil might play a major role in predicting the clinical outcome of breast cancer patients treated with neoadjuvant chemotherapy - Geng, Sheng-Kai (BMC Cancer, 2021)
BACKGROUND: This study was aimed to explore the predictive ability of tumor infiltrating neutrophil (TIN) in patients with breast cancer treated with neoadjuvant chemotherapy (NACT). Furthermore, the significance of TIN’s dynamic change before and after NACT was investigated. METHODS: Between January 2004 and December 2017, a total of 133 patients with breast cancer who underwent NACT before surgery were enrolled in this retrospective cohort. Eighty-nine of them were able to get the core needle biopsy (CNB) samples and all the pathological samples after surgery were available. TIN was detected by immunohistochemical staining of CD66b. The optimal cut-off value was determined via receiver operating characteristic (ROC) curve analysis. The association of clinicopathologic characteristics and chemotherapy efficiency was analyzed using X(2) test or Fisher’s exact test or t-test as appropriate, and the prognostic significances were assessed by univariate and multivariate analyses. RESULTS: Patients with higher TIN after NACT were confirmed to be significantly associated with worse prognosis (P = 0.002). After stratifying patients into two groups, high difference group was prone to have better chemotherapy efficiency (P < 0.001) and clinical outcome in both univariate (P = 0.002) and multivariate analyses (P = 0.003). CONCLUSIONS: In this study, higher TIN after NACT was confirmed to be associated with breast cancer patients’ worse chemotherapy efficiency and shorter disease-free survival (DFS). Furthermore, the TIN’s dynamic change before and after NACT was firstly proved to be a more accurate predictive marker compared with TIN after NACT. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12885-021-07789-6.